Covalent Linkage of Streptokinase to Recombinant Hirudin: A Novel Thrombolytic Agent with Antithrombotic Properties - Phaneuf, Matthew D; Ozaki, C Keith; Johnstone, Michael T; Loza, Jean-Pierre; Quist, William C; LoGerfo, Frank W (Thrombosis and Haemostasis, 1994)
In a continuing effort to create an agent which has both thrombolytic and antithrombotic properties, streptokinase (SK) was covalently bound to the potent antithrombin agent recombinant hirudin (rHir). Linkage of SK to 125I-rHir was accomplished via heterobifunctional crosslinkers in an average molar ratio of 1:1. The 125I-rHir-SK complex was purified from starting components by anion exchange and gel filtration chromatography. The major band containing covalently bound 125I-rHir had a molecular weight of 53 kDa as determined by SDS-PAGE and autoradiography. Biologic activity of each component was then assayed utilizing the chromogenic substrate for each compound. Complex bound 125I-rHir exhibited a 1.2 fold decrease in thrombin inhibition when compared to concentrations of, 25I-rHir greater than 3.13 nM. Complex bound i25I-SK, replacing the 125I label on rHir, displayed a 7.9-fold loss in plasminogen activation when compared to l25I-SK. These chromogenic assay results were not adversely altered in the presence of the converse compound’s substrate. The 125I-SK-rHir complex (examined at various concentrations) also demonstrated a 0. 17- to 17-fold greater affinity for thrombin immobilized onto Sepha- rose beads as compared to 125I-SK. These findings indicate the rHir-SK complex maintained both thrombolytic and antithrombin properties while also obtaining affinity for immobilized thrombin.